Perancangan Brand Identity Almas Media Sebagai Upaya Meningkatkan Brand Awareness - Wijardito, Virgiawan Tri; Bahruddin, Muhammad; Khoiriqqoh, Abdullah (Jurnal Art Nouveau, 2016)
AbstractThe purpose of designing brand identity Media Almas are designing visual identity of the company. The study was conducted with a qualitative research method is to conduct interviews, observation, documentation, recording, and literature to get the data used to support the manufacture of the design concept. From the data analysis found some keywords that refers to the visual communication strategy that will be used to reach the target audience ditujuh. After analysis of the data, was found creative concept of designing brand identity that is "Effective". Description effective concept is an action that has a function. The concept of "effective" aims to show that the Almas Media is printing that can provide solutions to all the needs of the audience promotion. The result of this scheme is to create a brand identity.Â Keyword: Brand identity, Almas media, Brand awareness